Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Catchment land use shapes lake-atmosphere thermal contrast and synchrony globally - Zhirong Yu; Gang Li; R. Iestyn Woolway; Jixiang Yang; Jiaming Hu; Juan Tao; Kun Shan; Kun Shi; Yunlin Zhang; Lian Feng; Erik Jeppesen; Qichao Zhou (Science Bulletin, 2026)

Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Auxiliary fermentation with Pediococcus acidilactici C1 reshapes flavor formation in sufu: An integrated metagenomic, flavoromic and non-targeted metabolomic deciphering - Chen Chen; Jiaming Li; Feng Wang; Mei Cheng; Tao Sheng; Zahoor Ahmed; Jingwei Hu; Yibin Zhou (Food Chemistry, 2026)

The extract of Cirsium setosum exerts antimicrobial activities on largemouth bass infected by Aeromonas veronii via regulating inflammatory and antioxidant responses - Yuhuan Qiu; Chutong Zhang; Dekun Tang; Dasen Li; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Targeted “ROS storm” in hypoxic periodontitis: A self-enhanced SDT/CDT synergistic platform based on triple-enzymatic Cu-Mo bimetallic nanozyme - Wei Wu; Tong Xu; Kehan Wu; Lilong Yang; Jiaming Wang; Kaidi Liang; Dan Yang; Piaoping Yang; Narisu Hu (Chemical Engineering Journal, 2026)

High Cholesterol Facilitates Ovarian Androgen Production and Contributes to the Development of Polycystic Ovary Syndrome - Yue Liu; Shourui Hu; Xiaofan Liang; Jiaming Zhang; Yiming Qin; Chunxuan Geng; Yuqing Zhang (Phenomics, 2026)

Nitrogen uptake preference of Avicennia marina and Aegiceras corniculatum in simulated saline water under varying salinities - Dejian Su; Jiaming Hu; Chutong Zhang; Yushuang Yang; Xiuru Zhu; Jian Guan; Yong Liu (Marine Environmental Research, 2026)

Paeoniae Radix Rubra extract inhibits largemouth bass ranavirus (LMBV) replication by suppressing inflammatory response and oxidative stress - Yang Liu; Dasen Li; Wenyan Liu; Chutong Zhang; Jiaming Liang; Karl Wah-Keung Tsim; Qiwei Qin; Weihui Hu (Fish & Shellfish Immunology, 2026)

Tracking 3D desiccation crack evolution and permeability dynamics in expansive soil - Yun Peng; Jiaming Zhang; Yi Luo; Tianle Liu; Mingjian Hu; Shuai Liu (Bulletin of Engineering Geology and the Environment, 2026)

Morphology–aware spatiotemporal prediction of cumulonimbus–related radar echoes using CSDP–Net - Deyi Wang; Xu Wang; Zhenhong Cheng; Xin Chang; Hongping Yuan; Jixiang Yang; Yi Liang; Jiaming Hu; Ting Zhang (Theoretical and Applied Climatology, 2026)

Research on the Support Mechanism of Tunnel Anchor Bolt Based on Physical Model Experiments and Continuous–Discontinuous Theory - Mingyi Wang; Shaobo Chai; Bo Hu; Chen Xu; Jiaming Wu; Yongqiang Zhou; Xiaodong Fu (Rock Mechanics and Rock Engineering, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

The E3 ligase RNF5 facilitates viral replication by suppressing innate immune responses in grouper - Yanqi Zhao; Xiaohui Zheng; Siting Wu; Minyao Bi; Jiaming Hu; Shaojie Liu; Jingguang Wei; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

A bead-based dendritic amplification system for multiplex miRNA detection - Feiyang Qian; Rui Zhu; Yao Lu; Tenghua Zhang; Yuqing Zhu; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2026)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Adaptive isoline interval optimization for precise contour segmentation and instance-level detection of Martian impact craters - Dong Chen; Fan Hu; Jiaming Na; Zhenxin Zhang; Zhen Cao; Liqiang Zhang; Zhizhong Kang; Jiju Poovvancheri; Norbert Pfeifer (Icarus, 2025)

Recycling waste poly(ethylene terephthalate) to prepare a Zn–MOF and its application as a nucleating agent for plastics and antibacterial agent on cotton fabrics - Xiaohui Lin; Jiaming Xu; Guoliang Sun; Jingjing Sun; Yi Xiao; Yanling Hu; Jinqing Yang; Yubiao Liao; Jianchun Liu; Mingyi Shang; Kun Wu (Journal of Environmental Chemical Engineering, 2025)

Mechanochemical treatment and valorization of hazardous fluorine from aluminum electrolyte in spent carbon anodes - Zhibo Liu; Zhenkun He; Bingqing Liu; Wenju Tao; Jiaxin Yang; Jiaming Li; Xianwei Hu; Zhaowen Wang (Journal of Environmental Chemical Engineering, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Dynamic interplay between core functional microbial succession and flavor metabolite formation in naturally fermented sufu: A multi-omics perspective - Chen Chen; Jiaming Li; Zahoor Ahmed; Changyue Deng; Feng Wang; Jingwei Hu; Yibin Zhou (Food Bioscience, 2025)

Robust smartphone-assisted cellulosic smart label for real-time monitoring shrimp freshness under low temperature and high humidity conditions - Yilin Wang; Jiaming Wu; Dong Lv; Yehan Tao; Jinwen Hu; Chenglong Fu; Xiaodong Xia; Jijuan Cao; Haisong Wang; Jian Du (Chemical Engineering Journal, 2025)

Exploring the effects of weather-driven dynamics of desiccation cracks on hydrological process of expansive clay slope: Insights from physical model test - Yi Luo; Xinyu Hou; Jiaming Zhang; Yujie Wang; Mingjian Hu; Guosheng Jiang; Chao-Sheng Tang (Journal of Hydrology, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Large-area crack-free photonic crystals coating on leather with brilliant and robust iridescent structural color - Jingyuan Hu; Yaqun Han; Xin Sun; Wenbo Wu; Jiaming Huyan; Suli Wu (Chemical Engineering Journal, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

GACraterNet: A collaborative geometry-attribute domain network for enhanced detection of Martian impact craters - Fan Hu; Dong Chen; Jiaming Na; Zhen Cao; Zhenxin Zhang; Liqiang Zhang; Zhizhong Kang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Ultrasensitive nanoenzymes-based lateral flow immunoassay platform for accurate detection of folic acid in human serum - Jinbo Cao; Tiemei Li; Xianglin Liao; Jiaming Zhang; Xixiang Yang; Huiqi Yan; Boyang Sun; Yanfei Li; Jiaxiang Huang; Yao Wang; Xiaogang Hu; Li Wang (Chemical Engineering Journal, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Effects of chlorpyrifos stress on the Eriocheir sinensis suffering from Metschnikowia bicuspidata infection - Jiaming Dong; Yuanyuan Tan; Chengcheng Feng; Qingbiao Hu; Yanhong Zhao; Jie Bao; Hongbo Jiang (Aquaculture, 2025)

Highly stable anode-free solid-state sodium batteries enabled by electrostatic shielding and nitrogenated interphase - Wuliang Feng; Caixia Li; Peiyao Wang; Jiaming Hu; Xuan Yu; Ying Zhang; Xingbao Zhu; Dengsong Zhang; Yongyao Xia; Yufeng Zhao (Chemical Engineering Journal, 2025)

Engineering cuttlefish melanin nanoparticles: A dual-action therapy for acute radiation syndrome and combined radiation-wound injuries via regulating Bcl-2 family proteins and caspases in the apoptotic process - Zhemeng Zhao; Bin Hu; Danfeng Zhang; Xinyue Cui; Wen Ding; Tongshuai Wang; Jingyi Wang; Ziyi Guo; Yingtang Zhou; Shige Wang; Jiaming Guo (Chemical Engineering Journal, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

High performance two photon polymerization resin designed for sub-micron precision and millimeter scale structure manufacturing - Jiaming Hu; Yang Gao; Lukun Wu; Bowen Zheng; Ning Li; Kai Du; Jing Li; Shuai Zhang (Chemical Engineering Journal, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

The impact of short-term exposure to criteria air pollutants on sleep disturbance among young adults: A nationwide analysis in 261 Chinese cities - Chunliang Wang; Kai Su; Linming Hu; Xinjie Dai; Xixian Fang; Chunhui Yang; Ruitong Zhang; Jiaming Liu; Junteng Zhou; Chenyu Xu; Hualu Gan; Lingyan Chen; et al. (Environmental Research, 2025)

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Mapping QTLs for stigma exsertion-related traits in two sets of CSSL populations of Oryza sativa cultivars using RSTEP-LRT method - Chunyu Jing; Mei Hai; Jiaming Shen; Xinru Li; Mengyuan Zhang; Changmin Hu; Qing Xu; Jianhua Jiang; Xiaojing Dang (Euphytica, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

SCARF: A new algorithm for continuous prediction of biomass dynamics using machine learning and Landsat time series - Yingchun Fu; Runhao Li; Zhe Zhu; Yufei Xue; Hu Ding; Xinyu Wang; Jiaming Na; Weijie Xia (Remote Sensing of Environment, 2024)

SbSeI for high-efficient photocatalytic degradation of multiple pollutants - Kang Li; Yue Gao; Zhongxin Dong; Huibo Zhang; Xudong Fan; Lei Xu; Jie Huang; Feng Teng; Haibo Fan; Jiaming Song; Chunmei Zhang; Xuexia He; et al. (Environmental Research, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

A novel sunflower-like nanocarrier based on dual milk-derived proteins for improved bio-accessibility, stability and antioxidant activity of anthocyanin - Shuangshuang Wang; Yi Ding; Liqing Xu; Jiaming Li; Minghui Zhang; Qisheng Hu; Haiyan Wang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Hydrocolloids, 2024)

Effects of dry-wet cycles on the mechanical properties of sandstone with unloading-induced damage - Gan Nan; Jiaming Zhang; Yi Luo; Xinlong Wang; Zhongyi Hu (Journal of Mountain Science, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

DNA Methylation is Involved in Sex Determination in Spinach - Keli Jia; Jiaming Duan; Guangqian Cheng; Heng Li; Shufen Li; Miao Hu (Biochemical Genetics, 2024)

Joint optimal allocation of regional water and land resources considering their mutual feed relationship - Chengguo Su; Zhenglei Hu; Wenlin Yuan; Jiaming Zhang; Denghua Yan; Huiliang Wang (Journal of Hydrology, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Synthesis and antiviral property of polysulfate-grafted maleimide-based enediynes - Zhuoyu Li; Zhe Ding; Haonan Cheng; Xiaofan Zhang; Houjun Zhang; Gary Wong; Yun Ding; Jiaming Lan; Aiguo Hu (Medicinal Chemistry Research, 2024)

An intelligent control method for PEMFC air supply subsystem to optimize dynamic response performance - Qingqing Su; Jiaming Zhou; Fengyan Yi; Donghai Hu; Dagang Lu; Guangping Wu; Caizhi Zhang; Bo Deng; Deming Cao (Fuel, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Characteristics and multi-factor mechanisms of dam construction on food web structure in cold-region rivers - Jiaming Hou; Qinghui Zeng; Peng Hu; Yunzhong Jiang; Yinglan A; Qin Yang; Baolong Zhao; Huan Liu; Zefan Yang; Xiaohui Qu (Journal of Hydrology, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

Cas-Rainbow: Cas12a-driven single-reaction multiplex detection system - Yuqing Zhu; Jianming Zhou; Yuxin Liang; Yao Lu; Shujun Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2024)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Recent advances in nanomaterial-enhanced persulfate activation for organic pollutants removal: Electron transfer, surface reactions, and radical generation - Dingren Ma; Ji Mei; Qiwen Liang; Yimu Jiao; Tianyu Hu; Jingchen Chen; Jiaming Wang; Hao Zhou; Qiyu Lian; Mingzhe Sun; Dehua Xia; Tianqi Wang (Journal of Environmental Chemical Engineering, 2023)

Coffee grounds-derived carbon quantum dots as peroxidase mimetics for colorimetric and fluorometric detection of ascorbic acid - Yuyan Zhu; Xiang Deng; Jiaming Chen; Zhiyuan Hu; Fengshou Wu (Food Chemistry, 2023)

Mechanical and internal structural damage evolution in cold recycled mixture under fatigue loading - Hu Yang; Liyan Shan; Lingwen Li; Zhiwei Li; Jiaming Yan (Journal of Cleaner Production, 2023)

A dual amplification-based CRISPR/Cas12a biosensor for sensitive detection of miRNA in prostate cancer - Yuqing Zhu; Xiaohe Zheng; Shujun Zhou; Wenjing Xiao; Xiaorui Sun; Jianming Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Analytica Chimica Acta, 2023)

Performance and response of coupled microbial fuel cells for enhanced anaerobic treatment of azo dye wastewater with simultaneous recovery of electrical energy - Liming Hu; Na Liu; Chang Li; Jiaming Mao; Meng Li; Yanbin Yun; Wenli Liu (Environmental Science and Pollution Research, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Surfactant-induced photocatalytic performance enhancement of europium oxide nanoparticles - Yishuai Jing; Tianxin Kang; Peng Hu; Haibo Fan; Feng Teng; Xin Zhao; Jiaming Song (Process Safety and Environmental Protection, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

Fracture behavior investigation of self-compacting rubberized concrete by DIC and mesoscale modeling - Xing Li; Fuheng Ma; Xudong Chen; Jiang Hu; Jiaming Wang (Journal of Cleaner Production, 2023)

Generation of reactive oxygen species through dissolved oxygen activation on defected porous carbon for efficient degradation of antibiotics - Jiaming Liu; Zhangwei Yao; Genping Qiu; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; Wenjing Yuan; Peihai Ju; Ruixi Lin; Hengcheng Zhou; et al. (Chemical Engineering Journal, 2023)

Systematical site investigation and temperature sensing in Pr3+-doped M3RE4O9 (M = Sr and Ba; RE = Sc, Y, Lu) - Xiangyu Han; Changqing Hu; Jiaming Wu; Shuxian Wang; Zhengmao Ye; Qingchun Yang (Chemical Engineering Journal, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Effects of nitrogen addition on soil faunal abundance: A global meta‐analysis - Junxi Hu; Shixing Zhou; Liehua Tie; Xiong Liu; Xing Liu; Anjiu Zhao; Jiaming Lai; Lin Xiao; Chengming You; Congde Huang (Global Ecology and Biogeography, 2022)
Aim Soil fauna has a wide range of ecosystem functions. Anthropogenic atmospheric nitrogen (N) deposition affects the structure and function of soil fauna by changing the microenvironment and resources. Given that soil faunal responses can vary considerably among taxonomic groups, N deposition rate, and ecosystems, however, there is little consensus. We aimed to evaluate the effects of N deposition on different soil faunal taxa across different terrestrial ecosystems. Location Global. Time period 1970–2021. Major taxa studied Soil fauna. Methods We conducted a meta‐analysis that yielded 264 observations from 43 publications. We evaluated the responses to N addition of soil faunal abundance for three different taxa (nematodes, mites, collembolans) in three ecosystem types (cropland, forest, and grassland). Results Our results showed an overall negative effect of N addition on soil fauna. However, the effect varied among soil faunal taxa. Specifically, N addition had no significant effects on the abundance of collembolans and mites in any ecosystem. On the other hand, N addition significantly reduced the abundance of all nematode trophic groups except bacterivores. The overall reduction of soil fauna is likely driven by the nematode response. The negative effects of N addition on nematode abundance were contingent on the N addition rate, N addition form, and ecosystem type. N addition decreased nematode abundance at N addition rates of more than 100 kg/ha/year. Inorganic N addition negatively affected nematode abundance. Finally, N addition had a greater adverse effect on nematodes in cropland and grassland compared to forest ecosystems. Main conclusions Our results demonstrate the overall negative effects of N addition on nematode abundance. Excessive N addition should be avoided in cropland and grassland management. Further, we suggest the application of organic fertilizer instead of inorganic fertilizer to minimize the N‐induced negative effects on soil nematodes.

Relative importance of branching enzyme isoforms in determining starch fine structure and physicochemical properties of indica rice - Piengtawan Tappiban; Yaqi Hu; Jiaming Deng; Jiajia Zhao; Yining Ying; Zhongwei Zhang; Feifei Xu; Jinsong Bao (Plant Molecular Biology, 2022)

Non-coding RNA in alcohol use disorder by affecting synaptic plasticity - Shuang Zhu; Jiaming Wu; Jian Hu (Experimental Brain Research, 2022)

Oxidative Damage Induced by Nano-titanium Dioxide in Rats and Mice: a Systematic Review and Meta-analysis - Hongmei An; Chunmei Ling; Mengchuan Xu; Mingjuan Hu; Haixia Wang; Jiaqing Liu; Guangling Song; Jiaming Liu (Biological Trace Element Research, 2020)

Space-for-time substitution in geomorphology - Xiaoli Huang; Guoan Tang; Tongxin Zhu; Hu Ding; Jiaming Na (Journal of Geographical Sciences, 2019)

Chlorella thermophila (Trebouxiophyceae, Chlorophyta), a novel thermo-tolerant Chlorella species isolated from an occupied rooftop incubator - Shuai Ma; Bingyin Han; Volker A. R. Huss; Xiaowen Hu; Xuepiao Sun; Jiaming Zhang (Hydrobiologia, 2015)